Pancreatic triglyceride lipase is involved in the virulence of the brown planthopper to rice plants - Long-yu YUAN; Yuan-hao HAO; Qiao-kui CHEN; Rui PANG; Wen-qing ZHANG (Journal of Integrative Agriculture, 2020)
The brown planthopper (BPH), Nilaparvata lugens, an important rice insect pest, can enhance its virulence to BPH-resistant rice within as short a span as several generations. Here, we cloned a pancreatic triglyceride lipase (PTL) gene (NlPTL) in N. lugens, and found that its mRNA level was higher in the high virulence population (fed on variety Rathu Heenati, P-RH) than in the low virulence population (fed on variety Taichung Native 1, P-TN1). Knocking down NlPTL caused BPH individuals to spend more time in non-penetration and the pathway phases and less time feeding on the phloem of rice plants; these changes consequently decreased food intake, lipid content, survival rate, and fecundity in the insects. These findings reveal for the first time that PTL in BPH is involved in its virulence to rice plants.